Tools for High Performance Computing 2012 - Cheptsov, Alexey; Brinkmann, Steffen; Gracia, José; Resch, Michael M.; Nagel, Wolfgang E. (Springer Berlin Heidelberg : Imprint: Springer, 2013)
The latest advances in the High Performance Computing hardware have significantly raised the level of available compute performance. At the same time, the growing hardware capabilities of modern supercomputing architectures have caused an increasing complexity of the parallel application development. Despite numerous efforts to improve and simplify parallel programming, there is still a lot of manual debugging and  tuning work required. This process  is supported by special software tools, facilitating debugging, performance analysis, and optimization and thus  making a major contribution to the development of  robust and efficient parallel software. This book introduces a selection of the tools, which were presented and discussed at the 6th International Parallel Tools Workshop, held in Stuttgart, Germany, 25-26 September 2012.